Propuesta de mejora para el proceso de picking en un centro de distribución (CEDI) de venta por catálogo de Cosméticos, enfocada en la metodología 5S (2023)
This work proposes an improvement in the picking time at a Distribution Center (CEDI) of a Catalog Sales Company, through the implementation of the 5S methodology with a focus on Lean Logistics principles.